OBSTETRICAL MANAGEMENT OF IMPERFECT CERVICAL DILATATION BY CERVICOTOMY IN A JERSEY COW - S. Sathishkumar; S. Rangasamy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A primiparous Jersey cow was brought in lateral recumbency with the history of straining and past occurrence of antepartum prolapse a week before. Vaginal examination revealed incomplete two finger cervical dilatation with a very thin cervical rim. Cervicotomy was performed to remove the live male fetus and the animal recovered uneventfully.